Analysis of Corn Production Determinants (Rural Lenteng Western District of Lenteng Sumenep) - Dody Tri Kurniawan (Agricultural Science, 2018)
Carbohydrate biggest producer of rice and wheat in addition to corn. Indonesia's corn consumption is not more than 2 kg per person per year compared with the expenditure of rice in Indonesia amounted to 85kg per person per year. The phenomenon occurs because there are many obstacles in the maize farming such as lack of capital, the cost of fertilizer and the price of corn. Lenteng Village West is one of the villages located in the District Lenteng with an agricultural land area and the most massive corn production. The land area reaches 1,027 hectares and the most massive corn production with the amount of 9243 tons. (BPP District of Lenteng 2017). The purpose of this study was to determine how much influence the capital, land, and labor to the production of corn in the village of West Lenteng. The approach is that researchers use associative data approach. The population in this study were farmers who were in Lenteng West with a total population of 150 farmers and a sample of 60 people with a level of tolerance (error) of 10%. Meanwhile, researchers in data collection using primary and secondary data, and data analysis Researchers using multiple linear regression method by using SPSS 16. Results of regression showed that the variables of capital, land, and labor in a positive and significant effect on maize production in the village of West Lenteng.